Análise do impacto dos desequilíbrios de carga nas perdas técnicas da distribuição e no processo de medição da energia elétrica - Novais, Isabela França (2023)
Over recent decades, electrical power concepts under nonsinusoidal and unbalanced conditions have been continually researched by several academics around the world. The results from these studies present a direct relationship between the performance of electric energy meters and the physical reality of the power balance between loads and sources. As such, this study presents a wide-ranging subject analysis that contemplates analytical, computer, and laboratory developments. This, in turn, opens the possibility of the physical representation of active power under unbalanced conditions, directly impacting the amount of active energy measured by the polyphase meters for billing purposes (from different manufacturers and models) and the composition of technical losses on distribution systems. The results showed that when using the fundamental active power of positive sequence as a reference, as suggested by IEEE Std. 1459/2010, none of the meters available worldwide correctly accounts for active energy. In this context, the study also presents the results from a power measurement campaign performed with 162 different low-voltage three-phase residential consumers located on five different electric energy utilities to understand the actual levels of current unbalance on this specific type of load. In this context, the main contributions of this work are related to (i) the quantification of measurement differences between active energy meters, highlighting the lack of equity in the measurement process of active energy under unbalanced conditions and (ii) the demonstration that the components of zero and negative sequence currents, produced by unbalanced loads, increase the technical losses of distribution systems. Furthermore, the results indicate the urgency of reviewing active energy measurement protocols for billing electricity consumers.